Directors’ Conflict of Interest and Its Implication for the Sustainability of a Company - OLUGASA, OLUBUKOLA; ABIRI - FRANKLIN, SOPHIA; OLANREWAJU, DEJI (Society & Sustainability, 2022)
Events on the Boards of directors in Nigeria have exposed diverse cases of conflict of interest and non-disclosure. Activities of some directors reveal that they do not know the boundaries of their allegiance to the companies that appointed them. This paper examined the role of directors' viz-a-viz conflict of interest and how it affects the sustainability of the companies. The doctrinal method was used to analyze the principles of corporate governance as it is related to the conflict of interest of those who are involved in the management. With the use of primary and secondary sources, the authors discussed the legal provisions addressing issues on conflict of interest, and the impact and implication of conflict of interest related to the organizations, the economy, and corporate sustainability. The paper found that lack of adherence to the provision of corporate governance framework had led to the pervasive cases of non-disclosure, conflict of interest, criminal liability, and extinction of the companies in extreme cases. This paper also offers recommendations for curbing the menace of conflict of interest in order to ensure corporate sustainability.